Effect of alcohol stimulation on salivary pellicle formation on human tooth enamel surface and its lubricating performance. (November 2017) - Zeng, Qihang; Zheng, Liang; Zhou, Jun; Xiao, Heng; Zheng, Jing; Zhou, Zhongrong
Abstract: This study was to investigate the salivary pellicle formation on the surface of human tooth enamel and its lubricating behavior under alcohol stimulation. Normal saliva and alcohol-stimulated saliva were collected from a young male volunteer after rinsing mouth with deionized water and different-concentration alcohol aqueous solution, respectively. Saliva-adsorption treatment was conducted in vitro on enamel surface to obtain salivary pellicle. Microscopic examinations and lubrication testing of salivary pellicle were performed by nanoscratch technology. Given that the pellicle lubricating properties are closely associated with its adhesion strength to substrates, the adhesion force between salivary pellicle and enamel was measured using an Atomic Force Microscopy. Compared with normal salivary pellicle, the salivary pellicle obtained from alcohol-stimulated saliva was not uniform anymore and even without any orderly multi-layer structure. Although alcohol stimulation improved the pellicle bonding to enamel surface, it caused the pellicle lubrication worse. In sum, the lubricating performance of salivary pellicle was more dependent on its orderly multi-layer structure from salivary protein self-assembly than its adhesion strength to enamel. Graphical abstract: fx1 Highlights: Alcohol had a negative effect on salivary pellicle formation and lubrication. Interestingly, alcohol caused an increasing adhesion of salivary proteins to enamel. Increased electrostatic interaction occurred after alcohol stimulation. Pellicle structure was more important than interfacial bonding for its lubrication.